2022
DOI: 10.46827/ejpe.v9i2.4560
|View full text |Cite
|
Sign up to set email alerts
|

The Influence on Physical Education State Anxiety and Leisure Motivation on Perceived Well-Being of Students

Abstract: The purpose of this study was to determine the influence of Physical Education state anxiety and leisure motivation on the perceived well-being of students. Utilizing quantitative, non-experimental design via correlational technique, data were obtained from 300 respondents of the study who are Grade 11 students in Physical Education in 4 public schools in Jose Abad Santos-2, Davao Occidental. The researcher utilized stratified random sampling and an online survey mode of data collection. The researcher also ut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 20 publications
1
2
0
Order By: Relevance
“…Students learn best when they can positively relate to lessons with these games as examples. It corroborates with the studies conducted by previous scholars(Avila, 2021;Barlizo & Osorno, 2022; Morales, 2015; Morales, 2016; Moro & Billote, 2023), who found that students stay motivated during the lesson with indigenous games integrated into the lesson.…”
supporting
confidence: 91%
See 2 more Smart Citations
“…Students learn best when they can positively relate to lessons with these games as examples. It corroborates with the studies conducted by previous scholars(Avila, 2021;Barlizo & Osorno, 2022; Morales, 2015; Morales, 2016; Moro & Billote, 2023), who found that students stay motivated during the lesson with indigenous games integrated into the lesson.…”
supporting
confidence: 91%
“…Thematic analysis was used to elicit and draw conclusions from the coded data. In particular, after the researchers determined the different perspectives of stakeholders, particularly the teachers (Agustin, 2020;Barlizo & Osorno, 2022;Booc et al, 2019;Cajetas-Saranza, 2020;Cerda, 2021;Morales, 2015;Mabborang et al, 2022;Moro & Billote, 2023;Mozar, 2020;Prestoza et al, 2020), students (Avila, 2021;Barlizo & Osorno, 2022;Booc et al, 2019;Morales, 2015), government officials (Mozar, 2020), and even others (or the authors themselves) (Almario, 2005;Cagas et al, 2022) and later make the coding, the data was analyzed thematically. Here, it was found that the Philippine traditional games can promote cultural heritage, facilitate convenient learning, and strengthen the foundation values, health, and socialization.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation